Meta-Analysis of the Effect of Internet-Based Self- Management on Blood Glucose Control in Type 2 Diabetes Mellitus Patients - Maulana, Moh; Tamtomo, Didik; Murti, Bhisma (Journal of Health Policy and Management, 2023)
Background: Diabetes mellitus is a chronic metabolic disorder or disease with numerous etiologies characterized by high blood glucose levels accompanied by lipid, protein, and carbohydrate metabolism disorders. Type 2 diabetes is the most common type of diabetes with about 90% of all diabetes cases. The International Diabetes Federation (IDF) estimates that the number of diabetics in the world can reach 783.7 million people while in Indonesia it is estimated to reach 28.57 million people in 2045. This number is an increase of 46% compared to 536.6 million in 2021. The study aims to discover how much influence internet-based self-management has on blood glucose control in type-2 diabetes mellitus patients.Subjects and Method: It was a meta-analysis study using PRISMA flowchart guidelines with the PICO formulation. P = type 2 diabetes mellitus patients. I = Internet-based self-management. C= No internet-based self-management. O= HbA1C. This study was conducted by searching for articles obtained from the MEDLINE/PubMed, Google Scholar, ProQuest, Science Direct, and Spinger Link databases with keywords and operators “Boolean electronic health record" OR "computerized" OR "healthcare system information" OR "mobile health" OR "mobile app" OR "Telehealth" AND "self-management" AND "Diabetes" OR "diabetes mellitus" OR " type 2 diabetes mellitus" OR "Type 2 diabetes. Based on the database, 10 articles met the inclusion criteria. The analysis was performed using Revman 5.3 software.Results: There were 10 articles from Asia, America, and Europe. A meta-analysis using Randomized Controlled Trials indicated that internet-based self-management significantly reduced HbA1c levels by 0.45 units (SMD= -0.45; CI 95%= -0.57 to -0.33= p<0.001).Conclusion: Internet-based management can reduce HbA1c levels of type 2 diabetes mellitus patients.Keywords: internet-based self-management, hba1c, type 2 diabetes mellitusCorrespondence:Moh Maulana. Masters Program in Public Health, Universitas Sebelas Maret. Jalan Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: maulana.rosy21@gmail.com. Mobile: +628-851 5667 1759Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.02.02